Coexistence of two clades of enterovirus D68 in pediatric Swedish patients in the summer and fall of 2014. Issue 10 (October 2015) - Dyrdak, Robert; Rotzén-Östlund, Maria; Samuelson, Agneta; Eriksson, Margareta; Albert, Jan
Abstract: In 2014, an outbreak of enterovirus D68 (EV-D68) was observed in North America, with cases of severe respiratory illness and a possible etiological link to cases of acute flaccid paralysis. EV-D68 has also been reported from European countries, but no data from Sweden are available. This study investigated respiratory specimens collected during July–October 2014 from 30 Swedish children aged 0–9 years who were positive for enterovirus and/or rhinovirus in routine clinical PCR. Seven samples were typed as EV-D68 by VP4/VP2 sequencing. Two genetically distinct EV-D68 variants coexisted. Six viruses belonged to clade B, the variant involved in the North American outbreak, and one virus belonged to clade A. Respiratory illness was the major symptom among EV-D68 infected patients and all fully recovered. This is the first report of EV-D68 in Sweden. Considering the current epidemiological situation, genotyping and specific EV-D68 testing should be considered in patients with severe respiratory illness who test positive for enterovirus or rhinovirus in routine diagnostics.